EFFECT OF KETOPROFEN ON THE PULMONARY ARTERIAL PRESSURE IN JERSEY CALVES SUBJECTED TO HIGH ALTITUD HYPOXIA - Lira M., Boris (2007)
The effect of ketoprofen, an antiprostaglandin substance that inhibits the enzyme ciclooxigenase, on the mean pulmonary arterial pressure (mPAP) was evaluated in 10, male Jersey calves, of 1-2 months of age. Calves were born at sea level and exposed during 3 days to an environmental hypoxia of 3,320 m of high altitude. A group of 5 animals received destiled water as placebo (Control group), and other group received ketoprofen in dose of 3 mg/kg body weight for 5 consecutive days while at sea level (Treated group). The mPAP was measured by cardiac cateterism at sea level and 3 days after arriving to the high altitude. The mean values of mPAP (mm Hg) at sea level were: Control group 19.00 ± 0.94 and Treated group 21.00 ± 3.39; whereas at the high altitude were: Control group 39.50 ± 6.00 and Treated group 31.25 ± 5.70, and without significant differences. When data of the two groups were joined and analysed together, the values for mPAP at sea level (20.00 ± 2.68) were statistically different (p<0.05) from those at day 3 of exposition to high altitude (35.28 ± 7.16). The results suggested that ketoprofen had not effect on mPAP in Jersey calves exposed during 3 days at high altitude hypoxia.